The Tholiban Brigade Political Da'wah Movement in Tasikmalaya - Dadang Kuswana (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This study aims to analyze the existence of the Tholiban Brigade movement in Tasikmalaya as a socio-religious movement. The research aims to answer the existence, motives, and transformation of the Tholiban Brigade da'wah movement in the political field. The research was conducted through a qualitative approach through descriptive methods. Data collection was carried out through observation, interviews, and literature study. The results showed that the legalization of Islamic law in the state's formal law was carried out by the Tholiban Brigade to actualize Islamic da'wah towards Islamic daulah. The legalization of Islamic law is carried out in aspirations, participation, coalitions, and regional political bargaining. The motive of the Tholiban Brigade political da'wah movement is the spirit of amar maruf nahi munkar both in individual and social spheres. This is an effort to change the social order towards Islamic life as a whole (kaffah). The transformation of the da'wah movement towards the Brigade Tholiban political movement is based on religious teachings that view Islam as a religion and state. The implication of this research is expected to map the existence of the Tholiban Brigade political da'wah movement in the national political constellation.Penelitian ini bertujuan untuk menganalisis eksistensi gerakan Brigade Tholiban di Tasikmalaya sebagai sebuah gerakan sosial keagamaan. Penelitian diarahkan pada upaya menjawab eksistensi, motif dan transformasi gerakan dakwah Brigade Tholiban dalam bidang politik. Penelitian dilakukan melalui pendekatan kualitatif melalui metode deskriptif. Pengumpulan data dilakukan melalui observasi, wawancara dan studi pustaka. Hasil penelitian menunjukkan bahwa legalisasi syariat Islam dalam hukum formal negara dilakukan oleh Brigade Tholiban sebagai upaya aktualisasi dakwah Islam menuju daulah Islamiyyah. Legalisasi syariat Islam dilakukan dalam bentuk aspirasi, partisipasi, koalisi dan bargaining politik daerah. Motif gerakan dakwah politik Brigade Tholiban adalah spirit amar maruf nahi munkar baik pada lingkup individual maupun sosial. Transformasi gerakan dakwah menuju gerakan politik Brigadi Tholiban didasarkan pada doktrin ajaran agama yang memandang Islam sebagai agama dan negara. Implikasi penelitian ini diharapkan mampu memetakan eksistensi gerakan dakwah politik Brigade Tholiban dalam konstalasi politik nasional.